Korean Learning Mobile Application for UiTM Students - Rosland, Siti Nurqamarina; Mohd Ghazalli, Hajar Izzati; Azhari, Amirah Zulaikha; Jamaluddin, Siti Syafiqah (2020)
The learning method that is not attractive lead learner to feel bored and do not want to read a book. There is also insufficient face to face a learning session which only two hours per week to learning Korean language with the lecturer. Therefore, this project is developing a mobile application to learn Korean language by using educational game technique. Korean learning Mobile application for UiTM students is intended to be used by UiTM students who enrolled for the Korean language subject, Korean language lecturer and anyone that interested in learning Korean language. The purpose of this system is to help users to learn Korean language more easily at anywhere and anytime. Currently, UiTM students used traditional book-based learning as a learning platform. This required much time to find the information since they need to read line by line of the book until they found the information that they require. Gamification techniques refer to the use of game symbols, game elements and concepts in a context other than games to increase motivation and interaction and influence user behaviour. The mobile application functionality has been evaluated. The result shows the system can run smoothly and meet the user's expectations. In conclusion, this application is able to use by Android users only, this limitation can be improved in the future so anyone either Android user or iOS user can use this application system.